The Antibacterial Efficacy of Miana Leaves Extract against Streptococcus Mutans - Khofifa Arda Anggelina Putri; Tyas Hestiningsih; Ibnu Ajiedarmo; Novita Idayani; Siti Rusdiana Puspa Dewi (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2023)
Introduction: Streptococcus mutans is the main bacterium that causes dental caries. Miana leaves antimicrobial compounds such as flavonoids, alkaloids, tannins, and saponins are expected to have antibacterial properties against the growth of Streptococcus mutans. Purpose: To determine the antibacterial effect of miana leaves extract on Streptococcus mutans growth. Methods: This study was an in vitro laboratory experimental study with a post-test only control group design. The treatment groups consisted of Miana leaves extract using concentrations of 3,125%, 6,25%, 12,5%, and 25%, positive control (0.2% chlorhexidine) and negative control (dimethyl sulfoxide/DMSO). Inhibition zone test was done using disc diffusion method. Results: The results showed that each concentration of Miana leaves extract had antibacterial properties. The largest diameter of the inhibitory zone was at 25% concentration, but significant smaller than 0.2% chlorhexidine. Conclusion: Miana leaves extract had an antibacterial effect against Streptococcus mutans.